Systematic Literature Review: Realistic Mathematics Education Approach for Enhancing Junior High Students' Critical Thinking Skills - Siswanto, Deny Hadi; Kintoko; Susetyawati, M.M. Endang (Indo-MathEdu Intellectuals Journal, 2025)
In the era of globalization, critical thinking skills in mathematics are essential. However, mathematics is often perceived as difficult and monotonous, prompting the need for teachers to employ engaging approaches, such as Realistic Mathematics Education (RME). RME connects mathematical concepts with real-life situations to enhance students' understanding and critical thinking skills. This study aims to analyze effectiveness of RME in improving junior high school students' critical thinking skills through a Systematic Literature Review (SLR) using the PRISMA approach. Data were collected from articles published between 2015 and 2025 in the WoS and Scopus databases, with 26 articles identified. The results indicate a growing number of RME-related publications, peaking in 2023 (10 articles). The most common research method was quasi-experimental (54%), with geometry as the primary topic (6 studies). Implemented strategies included e-worksheets, RME-based teaching materials, RME learning media, and RME learning models. This study confirms the effectiveness of RME in enhancing students’ critical thinking skills.